2011
DOI: 10.1016/j.jhep.2010.07.042
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection increases HCV-induced hepatocyte apoptosis

Abstract: Background and Aims-HCV related liver disease is one of the most important complications in persons with HIV, with accelerated fibrosis progression in coinfected persons compared to those with HCV alone. We hypothesized that HIV coinfection increases HCV related hepatocyte apoptosis and that HCV and HIV influence TRAIL signaling in hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 44 publications
5
44
0
Order By: Relevance
“…We recently demonstrated that co-infection with HCV and HIV stimulates DR4 and DR5 gene expression and subsequently activates caspase-3 signaling pathway, resulting in induction of mitochondrial apoptosis of human hepatocytes [18]. In this study, we demonstrate the significant contribution of caspase-8 activation to HCV-induced DR4/DR5-dependent hepatocyte apoptosis.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…We recently demonstrated that co-infection with HCV and HIV stimulates DR4 and DR5 gene expression and subsequently activates caspase-3 signaling pathway, resulting in induction of mitochondrial apoptosis of human hepatocytes [18]. In this study, we demonstrate the significant contribution of caspase-8 activation to HCV-induced DR4/DR5-dependent hepatocyte apoptosis.…”
Section: Introductionsupporting
confidence: 61%
“…Cell culture-derived HCV JFH-1 (HCVcc) used in this study was propagated and prepared, as described previously [18].…”
Section: Methodsmentioning
confidence: 99%
“…[48] In addition, exposure of HCV-infected hepatocytes to HIV leads to increased apoptosis and expression of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) and the TRAIL death receptors DR4 and DR5. [49, 50] Finally, infecting hepatocytes with HCV leads to induction of ROS and activation of p38 MAPK, JNK, ERK1/2 and NFκB pathways, which leads to increased TGF-β1. [51] In a similar manner, exposing hepatocytes to HIV directly leads to increased production of ROS, collagen, and tissue inhibitor of metalloproteinase 1 (TIMP1), an effect that is magnified by concurrent HCV exposure and can be blocked by ROS inhibition or siRNA to NFκB.…”
Section: Mechanisms Of Accelerated Fibrosismentioning
confidence: 99%
“…Relative risks were similarly increased for all major NHL subtypes (Marcucci and Mele, 2011). Although the mechanism of the interaction between HIV and HCV is not completely known, HIV increases the progression of HCV (Singal and Anand, 2009;Jang et al, 2010).…”
Section: Non Hodgkin Lymphomamentioning
confidence: 94%